Optimization Approach for Sensor Deployment Problem in Wireless Sensor Network - Puri, Vishal; Ramesh Babu, A.; Nagarajan, D.; Yadav, Rajesh (2018 International Conference on Circuits and Systems in Digital Enterprise Technology (ICCSDET), 2018)
Wireless sensor network (WSN) is generally a collection of spatially distributed and dedicated sensors to record and monitor the physical environmental condition, and the collected data is grouped at a central location. In fact, the environmental conditions such as sound, humidity, temperature, wind, pollution levels, etc. can be clearly determined by WSN. The principal objective of WSN is to organize the whole sensor nodes in their related positions, thereby developing an effective network. In WSN, Target COVerage (TCOV) and Network CONnectivity (NCON) are the main concern of Sensor Deployment problem. In sensor node deployment model, Target COVer-age (TCOV) and Network CONnectivity (NCON) are the main issue in WSNs that have initiate significant consideration in Sensor Deployment Problem. In this paper, ABC-WOA scheme algorithm are conveyed to find optimal locations for sensor nodes as an approximate solution. Main objective is provide suitable for improvement of different WSN application system. Finally, implementation of ABC-WOA proposed scheme in WSN are simulated in MATLAB and compare with other conventional methods such as GA and PSO models.